Rough Statistical Convergence of Double Sequences in Probabilistic Normed Spaces - Mondal, Rahul; Hossain, Nesar (Communications in Mathematics and Applications, 2023)
In this paper, we have defined rough convergence and rough statistical convergence of double sequences in probabilistic normed spaces which is more generalized version than the rough statistical convergence of double sequences in normed linear spaces. Also, we have defined rough statistical cluster points of double sequences and then, investigated some important results associated with the set of rough statistical limits of double sequences in these spaces. Moreover, in the same spaces, we have proved an important relation between the set of all rough statistical cluster points and rough statistical limits under certain condition.
Keywords: Probabilistic normed space; Rough statistical convergence of double sequences; Rough statistical cluster points of double sequences